Respuesta :

Answer:

EG = 42

Step-by-step explanation:

E___F____G

EG = EF + FG

10x -8 = (5x-2) + (3x+4)

10x - 8 = 8x +2

10x – 8x = 2 +8

2x = 10

x = 10/2

x = 5

We substitute the variable in the equation for EG .

EG = 10x – 8 = 10(5) – 8 = 50 – 8 = 42

I hope I helped you^_^

Answer:

Step-by-step explanation:

EG = EF + FG

10x - 8 = 5x - 2 + 3x + 4

10x - 8 = 5x + 3x - 2 + 4    {Combine like terms}

10x - 8 =  8x  + 2

Add 8 to both sides

10x = 8x + 2 + 8

10x = 8x + 10

Subtract 8x from both sides

10x - 8x = 10

2x = 10

Divide both sides by 2

x = 10/2

x = 5

EG = 10x - 8

     = 10*5 - 8

    = 50 - 8

EG = 42